2016
DOI: 10.1111/jcmm.13027
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatocyte‐like cells from human umbilical cord‐derived mesenchymal stem cells by defined microRNAs

Abstract: Generating functional hepatocyte‐like cells (HLCs) from mesenchymal stem cells (MSCs) is of great urgency for bio‐artificial liver support system (BALSS). Previously, we obtained HLCs from human umbilical cord‐derived MSCs by overexpressing seven microRNAs (HLC‐7) and characterized their liver functions in vitro and in vivo. Here, we aimed to screen out the optimal miRNA candidates for hepatic differentiation. We sequentially removed individual miRNAs from the pool and examined the effect of transfection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…Specifically, the regeneration process is induced by the activation of liver progenitor cells (LPCs) derived from endogenous progenitors (local cells) and or bone marrowderived circulating cells, particularly mesenchymal stem cells (MSCs) 3 . Studies have demonstrated that MSCs have high differentiation potential to specific cells, including primary hepatocytes 4 . These facts suggest that MSCs could accelerate the regeneration process of ALF.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the regeneration process is induced by the activation of liver progenitor cells (LPCs) derived from endogenous progenitors (local cells) and or bone marrowderived circulating cells, particularly mesenchymal stem cells (MSCs) 3 . Studies have demonstrated that MSCs have high differentiation potential to specific cells, including primary hepatocytes 4 . These facts suggest that MSCs could accelerate the regeneration process of ALF.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they showed that the differentiated cells can improve liver injury in an animal model. In their studies, hMSCs were directly converted into hepatocytes using a seven-miRNA combination and they claimed that in comparison with conventional methods, the seven-miRNA combination promoted hepatic differentiation of hMSCs more quickly and efficiently [79,80]. In another study, Khosravi et al used miR-106a, miR-574-3p, and miR-451 for hepatic differentiation for in vitro UC-MSCs and confirmed the production of ALB [81].…”
Section: Genetic Modifications Micrornas (Mirs)mentioning
confidence: 99%
“…Since then, a large number of studies tested the possibility of repopulating the liver with in vitro hepatic differentiated MSCs. To generate hepatocytes from MSC, a multitude of approaches has been used including the addition of cytokine cocktails [65,[86][87][88][89][90][91][92][93][94][95], small molecules [96], and/or microRNAs (miRNAs) [97][98][99] to the cell culture medium and recreation of the physicochemical characteristics of a hepatocyte niche micro-environment [100,101]. Generally, HLCs derived from MSCs possess some mature and fetal hepatocyte features as has been shown by transcriptome and functional studies [102,103].…”
Section: Hepatic Differentiated Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…In general, wild-type or immunodeficient mice without liver damage inducing transgene were used, and liver injury was caused by treatment with CCl 4 . A number of reports demonstrated presence of single cells or small groups of hALB positive cells throughout the liver (RI between 1 to 5%) 1 to 14 days after transplantation [86,89,97,98,100,105]. Most studies did not perform long-term follow-up analysis.…”
Section: Hepatic Differentiated Mesenchymal Stromal Cellsmentioning
confidence: 99%